Case note: The International Court of Justice’s 2022 reparations judgment in DRC v. Uganda - Safaa Jaber (22457695) (2025)
This case note examines the International Court of Justice’s (ICJ) 2022 reparations judgment in Democratic Republic of the Congo v. Uganda, analyzing the Court’s legal reasoning, its evidentiary approach, and the implications for future reparations cases. The 2022 judgment follows the ICJ’s 2005 ruling that found Uganda responsible for violations of international law during its military intervention in the Democratic Republic of the Congo (DRC). Given the failure of negotiations between the parties, the ICJ determined the amount of reparations owed, awarding a global sum of $325 million – substantially lower than the DRC’s claim. The case addresses complex legal and evidentiary questions, including the causal link between Uganda’s wrongful acts and the damages claimed, the standard and burden of proof for reparations, and categorizing harm. The Court examined four heads of damage, which were damage to persons, damage to property, damage to natural resources and macroeconomic damage, dismissing the latter due to insufficient proof of causation. A key aspect of the judgment was the ICJ’s adoption of a global sum approach – an uncommon approach in the Court’s practice. This case note assesses the lack of clear reasoning and methodology for determining the exact amount awarded for each head of damage. Additionally, the ICJ’s over-reliance on United Nations reports and its application of standards of proof raise concerns about consistency and clarity in reparations proceedings. This case sets a precedent for State responsibility in mass violations of international law but highlights challenges in quantifying harm and ensuring equitable reparations. The Court’s reasoning and methods in the case may influence future cases involving State responsibility, armed conflicts, and reparative justice under international law. Other Information Published in: International Review of the Red Cross License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1017/s1816383125000050